Directions for Improving the Activities of Regional banks in the Republic of Tatarstan - M. F. Gumerov; I. A. Rizvanova (Финансы: теория и практика, 2023)
The purpose of this study is to develop tools for assessing the state of regional banks and to justify decisions on the allocation of resources between their business areas by adapting existing methods of banking management to the new economic environment.The authors apply both general scientific methods (induction, deduction, analysis, synthesis) and special methods: systematic and retrospective analysis of existing developments in bank decisions.The results of the application of these methods are the mathematical models describing the functioning of the credit-deposit and transaction of commercial banks of Tatarstan in the past three years from the point of elasticity of actives and liabilities’ substitution. In the paper, we systematized the indicators of actives and liabilities of the five largest commercial banks in Tatarstan in 2019–2022, we approved the equations that characterize these actives and liabilities’ substitution elasticity in MS Excel.The conclusion is that in most cases, there is a unitary elasticity of their mutual substitution, which leads to the conclusion that the Tatarstan banking system is currently in the growth stage of a new life cycle, which began in 2014, after the Russian economy entered new realities due to sanctions pressure. The recommendations were formulated for the banks of Tatarstan in terms of improving the quality of loan portfolios in new conditions: they should improve the methods of making decisions about the loans for companies’ business activities which are first created.